Urban energy efficiency: a breakthrough vs. the global crisis - Pagani, Roberto (TECHNE - Journal of Technology for Architecture and Environment, 2011)
The environmental design and its complex multi-disciplinary consequences are central in the thinking of the responsibilities, which the Institutes of Knowledge are based on. It is no longer a battle to the forefront, just for the explorers. It is an acquired and consolidated culture, but from an operational standpoint there are many areas of innovation, development, affirmation still to develop. The article focuses on four central aspects of the new culture of energy efficiency in urban systems: the new global/local decision making, the sustainability in urban processes, the new skills for research and development, the growing interest of industries in innovative urban technologies. It provides the main trends in Europe and a vision of a possible exit from the complex socio-economic situation of today: a culture of complexity and energy innovation as factors of development.